Trends of Representation of Women in Professional Medical Societal Leadership in the United States and Europe - Sherna B. Menezes, MBBS; Ashleigh N. Shenton, MD; Allison G. Hays, MD; Cynthia C. Taub, MD, MBA (JACC: Advances)
Background: There continue to be significant gender disparities with women being underrepresented in medical professional society leadership roles, despite more women entering medical school. Objectives: This study aimed to elucidate the pattern of representation of women in medical society presidential positions in the United States and Europe over the past 50 years. It further examines gender-related trends in the field of cardiology and among medical trainees. Methods: Using publicly available data from major medical societies, we calculated the number of male and female presidents in major medical societies across most specialties in the United States and Europe over the past 50 years. We also examined cardiology societies specifically. These numbers and percentages were observed alongside those of medical students, internal medicine residents, cardiology fellows, and attending cardiologists. Results: Women constituted 4% and 0% of medical professional society presidents from 1974 to 2023 in the United States and Europe, respectively; this increased to a respective 32% and 40% in the past decade. For cardiology societies, the United States trended from 7% to 22% female presidents in the past 50 years, and Europe trended from 0% to 10%. Doctor of medicine and doctor of osteopathic medicine students have shown steady increases in women to now greater than 50%. Medicine residents, cardiology fellows, and cardiology attendings all have smaller percentages of women, though the number is increasing with time. Conclusions: While women remain underrepresented in medical professional society leadership in the United States and Europe, there is a trend toward more representation of women, which mirrors growth in this realm among medical trainees.